Men who inject opioids exhibit altered tRNA-Gly-GCC isoforms in semen. (20th January 2023) - Gornalusse, Germán; Spengler, Ryan M; Sandford, Erin; Kim, Yeseul; Levy, Claire; Tewari, Muneesh; Hladik, Florian; Vojtech, Lucia
Abstract: In addition to their role in protein translation, tRNAs can be cleaved into shorter, biologically active fragments called tRNA fragments (tRFs). Specific tRFs from spermatocytes can propagate metabolic disorders in second generations of mice. Thus, tRFs in germline cells are a mechanism of epigenetic inheritance. It has also been shown that stress and toxins can cause alterations in tRF patterns. We were therefore interested in whether injecting illicit drugs, a major stressor, impacts tRFs in germline cells. We sequenced RNA from spermatocytes and from semen-derived exosomes from people who inject illicit drugs (PWID) and from non-drug using controls, both groups of unknown fertility status. All PWID injected opioids daily, but most also used other illicit drugs. The tRF cleavage products from Gly-GCC tRNA were markedly different between spermatocytes from PWID compared to controls. Over 90% of reads in controls mapped to shorter Gly-GCC tRFs, while in PWID only 45% did. In contrast, only 4.1% of reads in controls mapped to a longer tRFs versus 45.6% in PWID. The long/short tRF ratio was significantly higher in PWID than controls (0.23 versus 0.16, P = 0.0128). We also report differential expression of a group of small nucleolar RNAs (snoRNAs) in semen-derived exosomes, including, among others, ACA14a, U19, and U3-3. Thus, PWID exhibited an altered cleavage pattern of tRNA-Gly-GCC in spermatocytes and an altered cargo of snoRNAs in semen-derived exosomes. Participants were not exclusively using opioids and were not matched with controls in terms of diet, chronic disease, or other stressors, so our finding are not conclusively linked to opioid use. However, all individuals in the PWID group did inject heroin daily. Our study indicates a potential for opioid injection and/or its associated multi-drug use habits and lifestyle changes to influence epigenetic inheritance.